REUSE INTENTION MODELS THROUGH CUSTOMER SATISFACTION DURING THE COVID-19 PANDEMIC: CASHBACK PROMOTION AND E-SERVICE QUALITY CASE STUDY: OVO ELECTRONIC MONEY IN JAKARTA - Hasyim, Umar; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2022)
The purpose of this study was to analyze the relationship between the model of reuse intention through customer satisfaction during the covid-19 pandemic through cashback promotions and e-service quality. The study involved 190 users of the OVO application. Researchers used Partial Least Square (PLS) as a technique used to analyze measurements and structural models. The results of this library research are that: Cashback promotion and e-service quality have a positive and significant effect on customer satisfaction and OVO electronic money users in Jakarta; Cashback promotions and e-service quality have a positive and significant impact on the reuse intention of OVO electronic money services in Jakarta; There is a positive and significant effect of customer satisfaction on the reuse intention of OVO electronic money services in Jakarta; Customer satisfaction can mediate the effect between cashback promotions and reuse intention of OVO electronic money services in Jakarta; Customer satisfaction can mediate the influence between e-service quality and reuse intention of OVO electronic money services in Jakarta.